Understanding the Impact of Remote Work on Team Dynamics: A Qualitative Analysis - Seger Santoso; Mia Christy Patricia; A Sigit Pramono Hadi (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2024)
The emergence of remote work as a prevalent mode of employment has brought about significant shifts in team dynamics within organizations. This qualitative analysis delves into the multifaceted effects of remote work on team interactions, communication, cohesion, and productivity. Through in-depth interviews and thematic analysis, this study explores the experiences and perceptions of team members and leaders regarding the challenges and opportunities presented by remote work. Findings reveal nuanced changes in collaboration patterns, the importance of technology in facilitating virtual teamwork, and the necessity for deliberate efforts to maintain social bonds and trust among team members. Furthermore, this research highlights the pivotal role of leadership in fostering an inclusive and supportive remote work environment. Understanding these dynamics is essential for organizations to adapt effectively to remote work paradigms and optimize team performance in the contemporary digital landscape.